CITRA DESTINASI DAN MINAT BERKUNJUNG KEMBALI : ANALISIS MODERASI KEPUASAN WISATAWAN - Retno Hernawati (LPPM Universitas Nusa Mandiri, 2025)
This study stems from the phenomenon of Gua Kristal’s remarkable tourism potential, yet the level of revisit intention remains relatively low. The purpose of this research is to analyze the influence of destination image on revisit intention by considering tourist satisfaction as a moderating variable. A quantitative approach was employed with the population consisting of all visitors to Gua Kristal. The sampling technique used was incidental sampling, resulting in 120 respondents. Data were collected through a questionnaire using a 5 point Likert scale, and analyzed using regression and Moderated Regression Analysis (MRA). The findings reveal that destination image has a significant effect on revisit intention, and tourist satisfaction is able to strengthen this influence. The implications highlight the importance for destination managers to maintain a positive image through cleanliness, safety, facilities, and effective promotion strategies. Moreover, tourist satisfaction must be prioritized by providing friendly services, adequate facilities, and enjoyable experiences, thereby enhancing visitors’ revisit intention.